Puerarin mitigates oxidative injuries, opening of mitochondrial permeability transition pores and pathological damage associated with liver and kidney in Xanthium strumarium-intoxicated rats - Alkac, Zeliha Keskin; Korkak, Fatih Ahmet; Dagoglu, Gurdal; Incili, Canan Akdeniz; Hark, Betul Dagoglu; Tanyildizi, Sadettin (Pergamon-Elsevier Science Ltd, 2022)
In this study, the therapeutic effects of puerarin on Xanthium strumarium toxicity, which can develop in many species and does not have a specific antidote, were investigated. A single dose of 100 g/kg X. strumarium seeds was administered by gavage to female Sprague-Dawley rats, 6 h following which 200 mg/kg puerarin was administered by the same route, with puerarin administration being repeated daily at the same time. After completing the application, the blood, liver and kidney tissues of the rats were examined. Further, the biochemical parameters, glucose, MDA, GSH, SOD, mitochondrial Ca2+ and mitochondrial permeability transition pore (mPTP) opening levels, apoptotic factors (TUNEL, Bax and Bcl-2), ATP synthase and histopathological changes of the experimental rats were examined. The results revealed that while the administration of X. strumarium resulted in increased blood AST, ALT, ALP, LDH, CK, BUN and creatinine levels, it decreased glucose levels. In addition, it increased the MDA levels in the tissues and significantly increased the oxidative stress levels by decreasing the GSH levels and SOD activity. X. strumarium caused an increase in the mitochondrial Ca2+ and mPTP opening levels. Moreover, it increased the immunohistochemically determined ATP synthase expression and histopathologically identified necrotic liver cell death rates. Owing to its antioxidant properties and inhibitory effects on mPTP opening, puerarin administered for therapeutic purposes decreased the oxidative damage caused by X. strumarium toxicity, blood biochemical parameter levels, mitochondrial Ca2+ levels, mPTP opening, ATP synthase expression and the percentage of necrotic cells. Hence, the reduction in the liver and kidney damage in X. strumarium toxicity by puerarin indicates its potential use as an antidote for X. strumarium poisoning.
Keywords: Xanthium strumarium; Rat; Puerarin; Histopathology; Immunohistochemistry